HUBUNGAN KEMAMPUAN BERPIKIR KRITIS DENGAN SELF CONFIDENCE SISWA KELAS IX MATERI BANGUN RUANG SISI LENGKUNG - Agung Setiawan; Rochmad; Nuriana Rachmani Dewi (Jurnal Pendidikan dan Kebudayaan Missio, 2021)
Mathematical thinking ability is the ability of thinking processes to think systematically, analyze arguments and come up with ideas with evidence to develop a logical mindset on what to do. This very important because students will be helped in thinking mathematically rationally in drawing conclusions and observing the problems that exist. It is also necessary to pay attention to self confidence which is the ability of students to solve existing problems. This study aims to determine the relationship between students 'mathematical critical thinking and students' self-confidence in learning mathematics for Grade IX students. This study uses quantitative research with a non-experimental approach, namely the correlation approach. The population of this study is class IX at SMP Al Madani with a sample of 21 people through the sampling technique, namely convenience sampling. Data collection techniques using observation, questionnaires, and tests. Data analysis used normality test and Pearson correlation test. Based on the research, the results obtained were 1) normality test with a significance of 0.586> 0.05, which means the data was normally distributed and 2) a correlation value of 0.520 and significant 0.016 <0.05, which means that there is a positive relationship between students' critical thinking skills and self-confidence. in mathematics learning. In other words, the higher the students 'critical thinking, the higher the students' self confidence. This can be explained also that students of SMP Al Madani have good self-confidence so that it can affect students' critical thinking skills in learning mathematics.